Unfetter the Poetry, that is how goth metal helps at understanding the classical authors - Kowalczyk, Andrzej (Free your mind: Reflections on language, literature and culture, 2022)
Nowadays it is difficult to encourage young people into poetry at school. The education systems lacks methods, which could make lyric poetry more attractive for students, because it may be difficult due to its form and specific figures of speech. The purpose of this article is to show the synergy between poems by classical German authors and the mix of music genres like goth metal and NDH (Neue Deutsche Härte), which is realised in the works of the German band Leichenwetter. The text also tries to describe their individual, eclectic music style and the uncommon selection of Poems for the lyrics. Another goal is to explain how the metal listeners as well as poetry fans can benefit from listening to Leichenwetter. As an example is shown the analysis of their interpretation of the sonnet Menschliches Elende by Andreas Gryphius.